Kinetic study for the oxidation of cyclohexanol and cyclohexanone with nitric acid to adipic acid - Pan, Detao; Li, Guangxiao; Su, Yuanhai; Wei, Huilong; Luo, Zhenghong (Chinese journal of chemical engineering, 2021)
The adipic acid is an important intermediate in the production of nylon, polyurethane and polyester resins. The industrial approach for preparing adipic acid is through the liquid catalytic oxidation of KA oil with nitric acid. In this work, a comprehensive model is developed for this reaction based on the kinetic study conducted in a continuous flow tubular reactor. The kinetic model fits well with the experimental results across the experimental conditions, and the average relative error between the calculated and experimental values is 5.7%. Results show that there was an induction period at the early stage of reaction. Moreover, it is found that at temperature range of 328–358 K, the formation rate of adipic acid strongly dependents on the temperature and nitric acid concentration. The developed model is used to predict the yield of adipic acid at 359–368 K. The work in this study could provide much knowledge for industrial tubular reactor design. [Display omitted]